Treatment-Related Mortality in Pediatric Acute-Lymphoblastic and Myeloid Leukemia: Experience from A Low- and Middle-Income Setting : Treatment-Related Mortality in Pediatric Acute-Lymphoblastic and Myeloid Leukemia - Gull, Sana; Ahmad, Alia; Iqbal, Luqman; Ul Ain, Rahat; Mushtaq, Waqar; Faizan, Mahwish (Pakistan Journal of Health Sciences, 2025)
Treatment-induced complications are challenging to manage in low-middle-income country (LMIC) settings, leading to higher mortality rates. Objectives: To ascertain the frequency, causes, and risk factors leading to treatment-related mortality (TRM) in children with acute leukemia (ALL and AML) in our setup. Methods: A Retrospective descriptive cohort study was done at the Hematology Oncology Department of the Children’s Hospital, Lahore. Using non-probability consecutive sampling, data of pediatric acute leukemia patients (<16 years of age) who experienced TRM during the study period were recorded. Results: Among TRM 136 (75%) had Acute-Lymphoblastic-Leukemia, and 45 (25%) had Acute-Myeloid-Leukemia. Median age of expiry 7.0 years (1–15years) with a Male-to-Female ratio 1.5:1. Underlying causes of TRM were Infection-related mortality in 168 (93%), Hemorrhage in 10 (5.5%), and Drug toxicity in 3 (1.5%). Under-nutrition (<10th centile) was found in 111 (61%) and 120 (67.4%) patients who were on active chemotherapy. Median hospital stays 10 days (1–45days) and median distance of residence to medical facility 222km (41–995km). Median values of hematological parameters at death: hemoglobin 8.0g/dl (2.6–14.7g/dl), WBC 0.57x103/mm3 (0.0-500), platelets 15x103/mm3 (0-503), and CRP 149mg/L(0.1–193mg/L). Significant factors associated were platelet counts (p=0.009), hemoglobin (p=0.001), and CRP (p=0.017). Conclusions: The Major cause of TRM in children with acute leukemia is infection. Noteworthy factors were male gender, residents of rural areas, cytopenia, high CRP, under-nutrition, and ongoing chemotherapy sessions. The majority of deaths occurred during Induction chemotherapy. Infection prevention/control and enhanced supportive care can result in decreasing TRM in acute leukemia.